(untitled) (Progressive Agriculture, 2013)
An In-house Indirect enzyme-linked immunosorbent assay (ELISA) was developed for the detection of serum antibody titre against Newcastle disease virus (NDV) and was compared its sensitivity and specificity with the commercially available NDV antibody detection ELISA kit (Biocheck®, USA). The reference NDV was purified by centrifugation, ultracentrifugation and by sucrose density gradient ultracentrifugation. This purified NDV was used for coating of 96-well flat bottomed microtitre plate and to raise hyperimmune sera (known) in Fayoumi chickens. In the standardization test, the antigen dilution of 10-6 and the serum dilution of 10-3 were considered to be optimum for the present ELISA system. The correlation regression analysis was performed to construct a standard curve equation where a good positive correlation was observed (r = 0.912, n = 8, P<0.01). The equation was used to convert corrected absorbance readings of the single working dilution (1 : 1000) directly into predicted ELISA antibody activity titres. In the sensitivity and specificity test, the serum dilution of 10-5 appeared to be the highest dilution which had the maximum lowest capacity to bind with the coated antigen of the present ELISA kit and only anti-NDV serum was found to bind with the coated antigen instead of serum of IBDV in the plate which revealed the high specificity of the developed In-house Indirect ELISA kit. In a comparative study with the 80 chicken sera samples, a significant positive correlation (r = 0.901, n = 80, P<0.01) was found between In-house Indirect ELISA and commercial ELISA kit (Biocheck®, USA). DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16467 Progress. Agric. 22(1 & 2): 55 - 64, 2011